Terrane‐controlled crustal shear wave splitting in Taiwan. Issue 2 (16th January 2016) - Okaya, David; Christensen, Nikolas I.; Ross, Zachary E.; Wu, Francis T.
Abstract: Taiwan is the result of arc‐continent collision associated with the convergence of the Philippine Sea plate with the eastern Eurasian plate continental margin. The locus of deformation is found in eastern Taiwan in the form of mountain building (Central Range) with underlying thickened lithosphere. Rapid tectonic exhumation in the Central Range has uncovered low‐to‐high‐grade metamorphic rocks marked by steep cleavage. We carried out a crustal seismic anisotropy study across Taiwan, producing a database of over 27, 000 local earthquake shear wave splitting measurements. Additionally, we carried out rock physics measurements of metamorphic outcrop samples to quantify shear wave rock anisotropy. We produced a map of station‐averaged splitting measurements across Taiwan. Patterns of fast shear wave directions correlate with tectonic terranes produced by plate convergence. Deformation‐related mineral‐preferred orientation in the metamorphic rocks produces a significant amount of the crustal anisotropy in the Taiwan collision zone. Key Points: Seismic anisotropy is ubiquitous throughout the Taiwan crust Crustal S wave splitting patterns correlate with arc collision tectonostratigraphic terranes Preferred mineral orientations cause S wave splitting in Taiwan metamorphic rocks